Type I Interferon Dependent hsa-miR-145-5p Downregulation Modulates MUC1 and TLR4 Overexpression in Salivary Glands From Sjögren’s Syndrome Patients - Jara, Daniela; Carvajal, Patricia; Castro, Isabel; Barrera, María-José; Aguilera, Sergio; González, Sergio; Molina, Claudio; Hermoso, Marcela; González, María-Julieta (Frontiers in Immunology, 2021)
Sjögren's syndrome (SS) is an autoimmune disease that mainly affects salivary glands (SG) and is characterized by overactivation of the type I interferon (IFN) pathway. Type I IFNs can decrease the levels of has-miR-145-5p, a miRNA with anti-inflammatory roles that is downregulated in SG from SS-patients. Two relevant targets of hsa-miR-145-5p, mucin 1 (MUC1) and toll-like receptor 4 (TLR4) are overexpressed in SS-patients and contribute to SG inflammation and dysfunction. This study aimed to evaluate if miR-145-5p modulates MUC1 and TLR4 overexpression in SG from SS-patients in a type I IFN dependent manner. Labial SG (LSG) biopsies from 9 SS-patients and 6 controls were analyzed. We determined hsa-miR-145-5p levels by TaqMan assays and the mRNA levels of MUC1, TLR4, IFN-α, IFN-β, and IFN-stimulated genes (MX1, IFIT1, IFI44, and IFI44L) by real time-PCR. We also performed in vitro assays using type I IFNs and chemically synthesized hsa-miR-145-5p mimics and inhibitors. We validated the decreased hsa-miR-145-5p levels in LSG from SS-patients, which inversely correlated with the type I IFN score, mRNA levels of IFN-β, MUC1, TLR4, and clinical parameters of SS-patients (Ro/La autoantibodies and focus score).IFN-α or IFN-β stimulation downregulated hsa-miR-145-5p and increased MUC1 and TLR4 mRNA levels. Hsa-miR-145-5p overexpression decreased MUC1 and TLR4 mRNA levels, while transfection with a hsa-miR-145-5p inhibitor increased mRNA levels. Our findings show that type I IFNs decrease hsa-miR-145-5p expression leading to upregulation of MUC1 and TLR4. Together, this suggests that type I interferon-dependent hsa-miR-145-5p downregulation contributes to the perpetuation of inflammation in LSG from SS-patients.